ANALISA PERILAKU KONSUMEN : STRATEGI MEMENANGKAN PERSAINGAN BISNIS DI ERA EKONOMI DIGITAL - Rachmad Santoso; Hisbulloh Ahlis Munawi; Ary Permatadeny Nevita (Universitas Islam Raden Rahmat, Malang, 2020)
The rapid development of information and communication technology has a major impact on consumer behavior in choosing and making decisions about buying and selling transactions. Information technology has made it possible to carry out various activities quickly, precisely and accurately, not limited to time and place, so that it is expected to increase performance and productivity. The increase in the number of internet users in Indonesia from 30 million people in 2009 to 171 million people in 2018 needs to be managed wisely, especially for companies that want to win business competition. Changes in consumer behavior related to how to obtain information and buying and selling transactions must be continuously researched to obtain accurate information about consumer wants and needs. This research was conducted to determine consumer behavior in carrying out activities, especially buying and selling, due to the development of information and communication technology. The survey was conducted using an online questionnaire to reach more respondents, more variety, wider distribution and shorter timeframes. The results show that there is a dependency of society on the internet and it has changed the way they access information and changed the way people buy and sell, from offline to online.